2012
DOI: 10.1111/j.1440-1681.2011.05630.x
|View full text |Cite
|
Sign up to set email alerts
|

Active chemical compounds of traditional Chinese medicine Herba Leonuri: implications for cardiovascular diseases

Abstract: 1. Herba Leonuri, a traditional Chinese medicine, has a long history of development and application in China. In particular, Herba Leonuri has been widely used in the treatment of gynaecological and obstetric disorders for thousands of years. Recent studies have shown that Herba Leonuri has many different effects. 2. Herba Leonuri contains several active components, including alkaloids, flavonoids, diterpenes compounds and fatty acids. Recent studies have shown that these molecules exert beneficial effects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Stachydrine, a major constituent of motherwort, can exhibit protective effects on vascular endothelial cells (ECs), as indicated by a recent study which reported that stachydrine reversed the Hcy-induced endothelial dysfunction and prevented eNOS uncoupling by increasing the expression of GTPCH1 and dihydrofolate reductase (DHFR) (Servillo et al, 2013;Xie et al, 2018). The low doses of stachydrine could inhibit hydrogen peroxide and induce myometrial smooth muscle cell apoptosis by upregulating Bcl-2 expression (Liu Xin et al, 2012). In the hippocampus, it could improve pathological changes by inhibiting inflammatory reactions after ischemia (Miao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stachydrine, a major constituent of motherwort, can exhibit protective effects on vascular endothelial cells (ECs), as indicated by a recent study which reported that stachydrine reversed the Hcy-induced endothelial dysfunction and prevented eNOS uncoupling by increasing the expression of GTPCH1 and dihydrofolate reductase (DHFR) (Servillo et al, 2013;Xie et al, 2018). The low doses of stachydrine could inhibit hydrogen peroxide and induce myometrial smooth muscle cell apoptosis by upregulating Bcl-2 expression (Liu Xin et al, 2012). In the hippocampus, it could improve pathological changes by inhibiting inflammatory reactions after ischemia (Miao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the hippocampus, it could improve pathological changes by inhibiting inflammatory reactions after ischemia (Miao et al, 2017). Additionally, stachydrine has been shown to exert antioxidant effects by reducing plasma lactate dehydrogenase (LDH) activity in the animal models of acute myocardial ischemia (Liu Xin et al, 2012;Zhao et al, 2017). However, there is a dearth of literature on whether stachydrine can function to treat stroke effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Leonurine appears to act via multiple molecular mechanisms, such as activation of the phosphatidylinositol 3-kinase/Akt survival pathway, preservation of superoxide dismutase and glutathione peroxidase activities and inhibition of intracellular Ca 2+ overload. Liu et al 19 comment that although the principal effects of leonurine in cardiovascular disease have been defined, further work is required to confirm its mechanisms of action.…”
Section: Introductionmentioning
confidence: 97%
“…The review by Liu et al 19 provides an update on the drug discovery arising from the traditional Chinese medicinal plant Herba leonuri, which has been used for centuries for gynaecological and obstetrical disorders. Among many alkaloids and flavonoids isolated from H. leonuri, leonurine is the unique alkaloid that has been studied extensively by the authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation